Estimation of economic life and feasibility of combine harvesters in Bangladesh deploying a unique web-based app - Habiba Akter; Md. Rostom Ali; Md. Shahinur Alam; Tumpa Rani Sarker; Sahabuddin Ahamed; Chayan Kumer Saha (Smart Agricultural Technology, 2024)
Combine harvester is one of the most crucial pieces of harvesting equipment in modern agriculture. Farmers and entrepreneurs employing a combine harvester need to focus on two pivotal factors: its profitability and optimal replacement time. Proper performance in this scenario can lead to prompt, and high-quality farm operations, enhancing income and simultaneously reducing product expenses significantly. This paper proposes a web-based application that would allow estimating the economic life and feasibility of combine harvesters in Bangladesh. The minimum cost value determination process has been used to estimate economic life by applying the double declining depreciation method. A high-level Python web framework has been used for the design and development of the software. The combine harvester exhibits a consistent economic life of 10 years for 300 to 450 hrs of annual use, with an increase in average yearly use from 300 to 450 hrs. As average yearly usage increases, the combine harvester's economic life declines drastically after 500 hrs of operation. Comparison with manual estimation shows that economic feasibility estimated by the web-based app provides more relevant data. The web-based app provides a useful tool for farmers, and entrepreneurs in Bangladesh to estimate the economic life and feasibility of combine harvesters, enabling better decision-making and improved managerial policies.